Abnormal metabolic connectivity in default mode network of right temporal lobe epilepsy - Wang, Xiaoyang; Lin, Dandan; Zhao, Chunlei; Li, Hui; Fu, Liyuan; Huang, Zhifeng; Xu, Shangwen (Frontiers in Neuroscience, 2023)
Temporal lobe epilepsy (TLE) is a common neurological disorder associated with dysfunction of default mode network (DMN). Metabolic connectivity measured by 18F-fluorodeoxyglucose Positron Emission Computed Tomography (18F-FDG PET) has been widely used to assess cumulative energy consumption and provide valuable insights into the pathophysiology of TLE. However, the metabolic connectivity mechanism of DMN in TLE is far from fully elucidated. In the present study, the metabolic connectivity mechanism of DMN in TLE is investigated using 18F-FDG PET. Participants included 40 TLE patients and 41 health controls (HC) who are age- and gender-matched. Graph theoretic analysis of the metabolic connectivity in DMN showed that regionally networks changed in the TLE group, including bilateral posterior cingulate gyrus, right inferior parietal gyrus, right angular gyrus and left precuneus. Besides, abnormal metabolic connections of DMN in the TLE group were revealed, containing bilateral hippocampus, bilateral posterior cingulate gyrus, bilateral angular gyrus, right medial of superior frontal gyrus and left inferior parietal gyrus. Taken together, the present study demonstrated the abnormal metabolic connectivity in DMN of TLE, which might provide further insights into the understanding the dysfunction mechanism and promote the treatment for TLE patients.